DELEGATED CASH CIRCULATION MODEL:EFFICIENCY OF AUTHORIZED BANKS - NAGORNY, PAVLO (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Despite the intensive introduction of IT technologies in the banking sector, resulting in the intensive development of non-cash payments, even with the constant increase in non-cash payments, the money supply outside banks is constantly increasing, thus the problem of ensuring quantity and quality of cash. Until 2016, the responsibility for ensuring the quality of cash in circulation and its exchangeability was assigned to the National Bank of Ukraine, one of the functions of which is to ensure the state monetary policy. In search of an effective policy in the organization of cash circulation, the Board of the National Bank of Ukraine in 2016 initiated the transition to a delegated model of cash circulation, which involves participation in cash circulation directly by the National Bank and authorized banks and SIT companies under the rules and under its control. The author of the article analyzes the results of implementation of the delegated model of cash circulation strategy in issues of cash quality assurance, its sufficiency outside banks, completeness of authorized banks’ functions in securing applications of commercial banks for reinforcement and acceptance of cash surpluses, sufficiency of developed measures. In researching the topic, the author concluded that there is currently a risk of losing control over the quality of cash in circulation, as well as providing cash in the required amount at the request of commercial banks due to imperfect relations between the regulator and authorized banks and technical and organizational unpreparedness. parties of authorized banks. According to the author, one of the reasons for the slow transition to the delegated model of cash circulation is that it is profitable for authorized banks to work for themselves, using the reserves of the National Bank. The solution of this problem by the National Bank is possible by making certain adjustments to the regulatory documentation.